Oxford Medicine Online 2018
DOI: 10.1093/med/9780199374847.003.0002
|View full text |Cite
|
Sign up to set email alerts
|

The Global Epidemiology of Drug Use in Prison

Abstract: This chapter provides an overview of drug use in prison. It is centered on illicit drug use in Europe, where the European Monitoring Centre for Drugs and Drug Addiction (EMCDDA) has been collecting aggregated data from various sources for 15 years. It also reviews, based on published literature, data from the four other global regions. A total of 59 studies from 31 countries in the five world regions were included for analysis. Results show that the prevalence of drug use varies greatly between studies. Lifeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 0 publications
7
18
0
1
Order By: Relevance
“…In our study, around one in three participants reported drug use during any imprisonment (either current or former), and almost one in four reported drug use during their current imprisonment. These findings are in line the Carpentiers and colleagues' recent review of 59 studies of drug use in European prisons (Carpentier et al, 2018), finding that drug use continues to some extent within the prison setting. The authors note that there are large variations between studies, but the proportion of inmates having used drugs in prison lies between 20% to 45% in most studies (Carpentier et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, around one in three participants reported drug use during any imprisonment (either current or former), and almost one in four reported drug use during their current imprisonment. These findings are in line the Carpentiers and colleagues' recent review of 59 studies of drug use in European prisons (Carpentier et al, 2018), finding that drug use continues to some extent within the prison setting. The authors note that there are large variations between studies, but the proportion of inmates having used drugs in prison lies between 20% to 45% in most studies (Carpentier et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…This is in line with international studies reporting that cannabis is the most commonly used illicit drug among people who experience incarceration, with between 14% and 70% having used it at some time in their lives (Carpentier et al, 2018). Whereas a small proportion of the general population has ever used heroin (EMCDDA, 2019), the lifetime prevalence among people in prison is typically much higher, with prevalence rates between 4% and 37% in European countries (Carpentier et al, 2018). Our findings add to a substantial body of literature highlighting the need for evidence-based drug treatment in prison settings, at a scale proportionate to need.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…People who inject drugs (PWID) are disproportionately represented among those who experience imprisonment [ 1 ]. Among people incarcerated in Australia, approximately half report ever injecting drugs [ 2 ] and approximately one quarter report injecting in the month prior to prison reception [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It might be attributed to different reasons. First, a significant percentage of prisoners are incarcerated due to drug-related crimes [ 9 ], therefore, there is a large population of PWID in prisons. Secondly, due to the lack of interventions and proper care and treatment services, shared injection is a common practice in prisons [ 10 ] and it has been proved that non-sterile shared injections is one of the main routes of the transmission of blood-borne diseases (BBD) [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%